Building Information Modeling-based Cost Estimation: The Case Study of the Guntung Payung Banjarbaru Community Health Center Building Project - Yuliana, Candra; Fathonah, Ibnu; Kartadipura, Retna Hapsari; Widiastuti, Endah (Engineering, Technology & Applied Science Research, 2025)
This study conducts a comparative analysis between a Business Information Modeling (BIM)-based and traditional cost estimation methods on the building structure of the Guntung Payung Banjabaru Health Center, Banjabaru City. The Tekla Structures (TS) software is utilized to carry out structural work calculations, including concrete, steel, and iron work, as well as the AHSP/HSPK working drawings from 2021. The BIM analysis results regarding the calculation time and cost differences were compared with the calculation results obtained with Microsoft Excel and AutoCAD. The two methods’ findings demonstrate that the cost difference is 12% for the concrete work and 13% for the iron/rebar work. It can be concluded that the BIM cost estimation method is more efficient, because its processing time is shorter and the calculation results are closer to the project needs compared to the conventional method.